Effect of low dose aspirin on maternal outcome in women at risk for developing pregnancy induced hypertension - Pradhan, Madhusmita; V., Kishore S.; Champatiray, Jyotiranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pre-eclampsia is not totally a preventable disease. It is found more related to chains of social ills such as poor maternal nutrition, limited or no antenatal care and poor reproductive education. However, some specific “high-risk” factors leading to pregnancy induced hypertension (PIH) may be identified in individuals which include and not limited to young and elderly primigravida, multiple pregnancy, diabetes, Rh incompatibility, new paternity, pre-existing vascular or renal disease, family history of hypertension, pre-eclampsia and eclampsia, obesity, thrombophilia. Low dose aspirin given in 2nd trimester in these high-risk women is anticipated to prevent the development of PIH. Methods: This prospective randomized controlled trial was conducted in the department of obstetrics and gynecology, SCB MC and Hospital, Cuttack during November 2018 to October 2019. Pregnant women between the gestational age of 13th to 28th weeks were screened for risk factors and included in this study. Low dose aspirin of 60 mg daily till delivery was given to pregnant women who consented to be a part of study randomly with the other group having placebo. Results: Protienuric hypertension was high in control group who did not receive aspirin. Low dose aspirin significantly reduces PIH in high-risk group (3.48% in case versus 23.52% in control). Low dose aspirin was not associated with significant increase in placental bleeding. Low dose aspirin was generally safe for the fetus and new born infant with no evidence of an increased likelihood of bleeding. Conclusions: Low dose aspirin has a definite role in the prevention of PIH in high risk pregnancy. Low dose aspirin reduces the incidence of PIH. Low dose aspirin can be considered a safe drug without any deleterious side effect for mother and the fetus. Benefits of prevention of PIH, justifies its administration in women at high risk.